Replication profile of PCDH11X and PCDH11Y, a gene pair located in the non-pseudoautosomal homologous region Xq21.3/Yp11.2. - Wilson, N; Ross, L; Close, J; Mott, R; Crow, T; Volpi, E (2007)
In order to investigate the replication timing properties of PCDH11X and PCDH11Y, a pair of protocadherin genes located in the hominid-specific non-pseudoautosomal homologous region Xq21.3/Yp11.2, we conducted a FISH-based comparative study in different human and non-human primate (Gorilla gorilla) cell types. The replication profiles of three genes from different regions of chromosome X (ZFX, XIST and ATRX) were used as terms of reference. Particular emphasis was given to the evaluation of allelic replication asynchrony in relation to the inactivation status of each gene. The human cell types analysed include neuronal cells and ICF syndrome cells, considered to be a model system for the study of X inactivation. PCDH11 appeared to be generally characterized by replication asynchrony in both male and female cells, and no significant differences were observed between human and gorilla, in which this gene lacks X-Y homologous status. However, in differentiated human neuroblastoma and cerebral cortical cells PCDH11X replication profile showed a significant shift towards allelic synchrony. Our data are relevant to the complex relationship between X-inactivation, as a chromosome-wide phenomenon, and asynchrony of replication and expression status of single genes on chromosome X.